Pengaruh Kualitas Produk, Citra merek dan Persepsi Harga Terhadap Kepuasan Pelanggan Produk Smartphone Xiaomi: Studi pada Konsumen Produk Xiaomi di Kabupaten Jepara - Arya Bagus Suryawan; Euis Soliha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study was conducted to analyze the effect of product quality, brand image and price perception on customer satisfaction of Xiaomi HP in Jepara Regency. The sample in this study amounted to 100 respondents with the sampling method using Non probability Sampling technique and using google form as a medium with a questionnaire method. This research analysis uses multiple linear regression analysis. The results of the research instrument test show that all indicators are valid and all variables are reliable. Based on multiple regression analysis obtained results: (1) product quality has no significant effect on customer satisfaction (2) brand image has a positive and significant effect on customer satisfaction (3) price perception has a positive and significant effect on customer satisfaction.